Expectativas inflacionárias e a política monetária sob o regime de metas de inflação - Cíntia Aparecida Furtado Gaio (2015)
The anchoring of inflation expectations is one of the main objectives of Inflation Targeting. The credibility of monetary policy is essential for this anchoring, in order to achieve low and stable inflation, lower inflationary impacts of shocks and lower disinflation costs. In order to verify the anchoring of inflation expectations in Brazil, a simple test was carried out on the credibility of monetary policy, based on market expectations and implicit inflation on financial assets. The conduct of monetary policy was assessed by estimating the central bank's reaction function, while the role of expectations on inflationary dynamics was studied by regressing inflation on its determinants. Estimates were performed using robust error regressions for heteroscedasticity and autocorrelation of the residuals. In addition, the stability of the parameters was analyzed by subperiod regressions, rolling regressions and recursive regressions. The results showed that inflation expectations are not anchored to the targets since 2010 approximately, and possibly were anchored to the ceiling of the range. They showed evidence regarding changes in the reaction of the monetary authority to the deviations of inflation expectations, causing the credibility of monetary policy achieved to set back after the 2008 crisis. These changes resulted in high inflation, positive and growing deviations from expectations to the targets and impacts on the inflationary dynamics. As a result, in 2015 Brazilian Central Bank is confronting the difficult choice between stabilizing inflation and recovering of the product, in an environment of greater uncertainty.